Green Marketing terhadap Keputusan Pembelian Mie Instan Lemonilo di Sumbawa Besar - Indah Wulan Saputri; Hartini, Hartini (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of Green Lifestyle, Green Product, and Green Advertising on the purchasing decisions of Lemonilo instant noodles in Sumbawa Regency. This research employs a quantitative method with an associative approach. Primary data were collected through questionnaires distributed to 130 respondents selected using purposive sampling. The criteria included consumers who had purchased Lemonilo products within the past six months and were domiciled in Sumbawa. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method via the SmartPLS 4 application. The results indicate that Green Lifestyle, Green Product, and Green Advertising each have a positive and significant partial effect on the purchasing decision of Lemonilo instant noodles in Sumbawa Regency. Green Product emerged as the most dominant variable, followed by Green Advertising, while Green Lifestyle showed the least influence. These findings highlight the importance of green marketing strategies in influencing consumer behavior. The implications suggest that companies should enhance product information transparency, promote sustainable lifestyle education, and strengthen marketing communication based on environmental values.